2013
DOI: 10.1007/s00572-013-0523-x
|View full text |Cite
|
Sign up to set email alerts
|

Maize development and grain quality are differentially affected by mycorrhizal fungi and a growth-promoting pseudomonad in the field

Abstract: Arbuscular mycorrhizal (AM) fungi and plant growth-promoting bacteria (PGPB) can increase the growth and yield of major crops, and improve the quality of fruits and leaves. However, little is known about their impact on seed composition. Plants were inoculated with AM fungi and/or the bacterial strain Pseudomonas fluorescens Pf4 and harvested after 7 months of growth in open-field conditions. Plant growth parameters were measured (biomass, length and circumference of spikes, number of grains per cob, grain yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 63 publications
10
55
1
Order By: Relevance
“…Presently, the role of AMF in influencing soil fertility, crop productivity, yield quality and protection against environmental stresses is widely acknowledged (van der Heijden et al 1998;Smith and Read 2008;Giovannetti et al 2012;Berta et al 2013). AMF contribution to crop growth and productivity can be influenced by both interspecific and intraspecific differences (Munkvold et al 2004;Vogelsang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the role of AMF in influencing soil fertility, crop productivity, yield quality and protection against environmental stresses is widely acknowledged (van der Heijden et al 1998;Smith and Read 2008;Giovannetti et al 2012;Berta et al 2013). AMF contribution to crop growth and productivity can be influenced by both interspecific and intraspecific differences (Munkvold et al 2004;Vogelsang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…M fungi from fertilized soil produced fewer hyphae and arbuscules and consequently supplied their host with fewer inorganic nutrients from the soil (Johnson, 1993). Concerning the mycorrhizal colonization of inoculated plants of this trial, F (87.8%) was lower than the expected based on some similar available studies in field conditions (Berta et al, 2014). The significant, but not remarkable differences between the rates of root colonization in inoculated plants respect to uninoculated ones may be explicated considering the difficulty the AM inoculum has to face in soil colonization.…”
Section: Mycorrhizal Root Colonizationmentioning
confidence: 57%
“…As a matter of fact, mycorrhizal index (F%) values registered in uninoculated maize were very high (80.3%), when compared with related studies. The AM colonization of uninoculated maize produced under field conditions varied according to different Authors: 39.7% in maize as following crop after Trifolium alexandrinum (Pellegrino et al, 2011), 25.1-61.2% in two consecutive years (Sousa et al, 2012), 45% (Cheeke et al, 2013) and 55.3% (Berta et al, 2014). Autochthonous AM fungi can colonize roots of most plant species, including maize (Smith and Read, 2008), but it was clearly demonstrated that the soils exposed to intensive cultivation have extremely low number of indigenous AM fungal propagules (Li and Zhao, 2005;Subramanian et al, 2009).…”
Section: Mycorrhizal Root Colonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of a consortium of AMF and the plant growth-promoting rhizobacteria (PGPR) was studied by Mäder et al [47] and found to positively affect crop yield, grain, soil quality and nutrient uptake of the staple food crop wheat (Triticum aestivum (L.)) in a rotation with either rice (Oriza sativa (L.)) or black gram (Vigna mungo (L.) Hepper). Recently, Berta et al [48] have shown that the inoculation with MC containing bacteria and AMF promote the growth of maize cultivated in field conditions and differentially affect the grain nutritional content.…”
Section: Mycorrhizal Inoculants As Bio-fertilizersmentioning
confidence: 99%